THE ANALYSIS OF RELATIONSHIP BETWEEN MOTHER AND CHILD AND ITS IMPACT ON THE FORMATION OF GENDER STEREOTYPES IN THE CONTEXT OF PSYCHOANALYTIC FEMINISM - L. Bulanova-Duvalko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. The article analyzes the influence of the experience of motherhood on formation steady sexual arrangements and stereotypical models of femininity and masculinity in society in the context of the psychoanalytic feminism. In particular, the importance of philosophical analysis of mother-child interrelations as the subjects of motherhood experience facilitates the understanding of mechanisms for construction and reproduction of the sexual arrangements and stereotyped gender roles is covered. Moreover, the influence of separation and individuation processes in the mother-child interrelations on the reproduction of patriarchy in social relations is considered. Research methodology. The basis of the research is a methodology of the psychoanalytic feminism as well as content analysis and a systematic method. Scientific novelty of the research lies in studying and systematizing the key theses of stereotypical manifestations of femininity theoretical substantiation from the perspective of psychoanalytic feminism that had not been presented within the national scientific thought. The research handles the following tasks: 1)to define the main directions of polemics of the psychoanalytic feminism and psychoanalytic concepts of Sigmund Freud and Jacques Laca; 2) to highlight the major spheres of the psychoanalytic feminism scientific interest;3) to consider the features of theory about the influence of the human psyche development during the pre-oedipal stage on producing the constant sexual arrangements in the perspective of the Anglo-American tradition of the psychoanalytic feminism; 4) to describe the main aspects of the theory about constructing femininity in the French feminism studies; 5) to analyze different ways to overcome the patriarchal symbolic order suggested by the psychoanalytic feminism. Conclusions. The research found that despite the adherence to a particular psychoanalytic theory the scholars agree that the pre-oedipal stage of psychosexual development is crucial for producing the stereotyped models of femininity and masculinity that are followed by a person during their life. Most of the researches emphasize the essential value of bonds between mother and daughter for sexual differentiation and feminization of daughter during the subsequent periods of psychosexual development.